Perbedaan Self Disclosure pada Mahasiswa yang menggunakan Pseudonym Account X Berdasarkan Jenis Kelamin - Tasya Cahya Salsabila; Ninda Yosa Putri; Nurhasanah Putri; Mario Pratama (CV. ITTC INDONESIA, 2026)
Self-disclosure is the act of an individual sharing personal information that is typically unknown to others. This study aims to analyze the differences in self-disclosure among students using pseudonymous accounts on platform X, based on gender, at Universitas Negeri Padang. Utilizing a quantitative method and a comparative approach, the study involved 19 students divided into two groups: male and female. Data analysis using the Mann-Whitney U test revealed no significant differences in self-disclosure between the two groups (significance value 0.539 > 0.05). Although female students had a slightly higher mean score compared to male students, the statistical test results indicated that this difference was not significant. The findings of this study suggest that gender is not a primary factor determining the level of self-disclosure in the context of this sample.